2004
DOI: 10.1074/jbc.m401259200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Sphingosine Kinase-1 by DNA Damage

Abstract: Sphingosine kinase 1 (SK1), a key enzyme in sphingosine 1-phosphate (S1P) synthesis, regulates various aspects of cell behavior, including cell survival and proliferation. DNA damaging anti-neoplastic agents have been shown to induce p53, ceramide levels, and apoptosis; however, the effects of anti-neoplastic agents on SK have not been assessed. In this study, we investigated the effects of a DNA damaging agent, actinomycin D (Act D), on the function of sphingosine kinase (SK1). Act D caused a reduction in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
121
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 32 publications
13
121
0
Order By: Relevance
“…For instance, Hara et al (25) have reported that g-radiation causes a p53-dependent increase in acid ceramidase, an enzyme that hydrolyzes proapoptotic ceramide to form growth-promoting sphingosine. Reciprocally, previous studies have shown the p53-dependent increases in ceramide levels via down-regulation of sphingosine-kinase-1, thus forming the concept that p53 promotes ceramide generation rather than promoting its breakdown or abrogating its synthesis (52). Thus, the role p53 seems to play in ceramide metabolism is currently unclear and therefore warrants further examination.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, Hara et al (25) have reported that g-radiation causes a p53-dependent increase in acid ceramidase, an enzyme that hydrolyzes proapoptotic ceramide to form growth-promoting sphingosine. Reciprocally, previous studies have shown the p53-dependent increases in ceramide levels via down-regulation of sphingosine-kinase-1, thus forming the concept that p53 promotes ceramide generation rather than promoting its breakdown or abrogating its synthesis (52). Thus, the role p53 seems to play in ceramide metabolism is currently unclear and therefore warrants further examination.…”
Section: Discussionmentioning
confidence: 96%
“…prolonged ceramide production (11,51), suggesting that de novo ceramide synthesis rather than a sphingomyelinasemediated mechanism may be involved. Alternatively, it has been proposed that elevated ceramide levels following DNA damage is partly the result of the p53-mediated down-regulation of sphingosine-kinase-1, which is involved in the catabolism of ceramide to sphingosine-1-phosphate (52). The result of sphingosine-kinase-1 down-regulation by these means would therefore be through ceramide accumulation versus alterations in ceramide synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…While this work was in completion, in line with our findings, a downregulation of SphK1 protein in the Molt-4 leukemia cells following treatment with DNA damaging agents in a p53-dependent manner was reported. 32 However, HL-60 cells are p53-null hence indicating that SphK1 inhibition is independent of tumor supressor p53 expression in these cells. Additionally, our recent data in prostate cancer cells show SphK1 inhibition in response to chemotherapeutics regardless of the p53 status of the cells (Pchejetski D and Cuvillier O, personal results).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, overexpression of SphK1 in A-375 cells had no effect on Bcl-2 expression, indicating that Bcl-2 might be upstream of SphK1. Interestingly, overexpression of Bcl-2 or failure to upregulate p53 MOLT-4 leukemia cells following DNA damage induced by actinomycin D inhibits the activation of proteases and, subsequently, prevents SphK1 proteolysis (Taha et al, 2004). To explore the potential role of endogenous Bcl-2 in the regulation of SphK1 expression, Bcl-2 was specifically downregulated with siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this correlated with SphK1 activity that was increased after 8 and 24 h of doxycycline treatment by twofold and 2.5-fold, respectively (Figure 7c). Nonspecific effects of doxycycline were excluded as vector-transfected Bro-Tet-On cells showed no increase in Bcl-2 (Figure 7d Recently, it has been reported that overexpression of Bcl-2 protects SphK1 from DNA damage-induced proteolysis (Taha et al, 2004). As overexpression of Bcl-2 increases SphK1 activity (Figure 7c), it was of interest to determine whether endogenous Bcl-2 might regulate basal SphK1 expression.…”
Section: Correlation Of Bcl-2 Expression and Sphk1 In Melanoma Cellsmentioning
confidence: 99%